Comparitive Analysis of Cytological Profile of Sputum of Shcoolchildren with Bronchial Asthma under Eosinophilic Neytrophilic Inflammation of Airways - L.O. Bezrukov; O.K. Koloskova; Ye.P. Ortemenka (Zaslavsky O.Yu., 2012)
In pulmonaty and allergy department of regional children clinical hospital in inter-attack period there were examined 116 schoolchildren with bronchial asthma and 11 healthy children. It has been established that inflammatory process of airways in bronchial asthma has remained even against the background of seeming clinical well-being, it's mediated by neutrophils, alveolar macrophages, eosinophils and other cells. The index of 3 % and more of eosinophils in the sputum should be recommended for identification of eosinophilic type of bronchial inflammation.